Bottom-Up Design of Composite Supraparticles for Powder-Based Additive Manufacturing - Canziani, Herbert; Chiera, Salvatore; Schuffenhauer, Thomas; Kopp, Sebastian-Paul; Metzger, Florian; Bück, Andreas; Schmidt, Michael; Vogel, Nicolas (Small, 2020)
Additive manufacturing promises high flexibility and customized product design. Powder bed fusion processes use a laser to melt a polymer powder at predefined locations and iterate the scheme to build 3D objects. The design of flowable powders is a critical parameter for a successful fabrication process that currently limits the choice of available materials. Here, a bottom-up process is introduced to fabricate tailored polymer- and composite supraparticles for powder-based additive manufacturing processes by controlled aggregation of colloidal primary particles. These supraparticles exhibit a near-spherical shape and tailored composition, morphology, and surface roughness. These parameters can be precisely controlled by the mixing and size ratio of the primary particles. Polystyrene/silica composite particles are chosen as a model system to establish structure–property relations connecting shape, morphology, and surface roughness to the adhesion within the powder, which is accessed by tensile strength measurements. The adhesive properties are then connected to powder flowability and it is shown that the resulting powders allow the formation of dense powder films with uniform coverage. Finally, successful powder bed fusion is demonstrated by producing macroscopic single layer specimens with uniform distribution of nanoscale silica additives.
CRIS-Team Scopus Importer:2020-07-10
Keywords: additive manufacturing; composite powders; nanoscale; spray drying; supraparticles

From Sticky to Slippery: Self-Functionalizing Lubricants for in Situ Fabrication of Liquid-Infused Surfaces - Chiera, Salvatore; Koch, Vanessa; Bleyer, Gudrun; Walter, Teresa; Bittner, Carina; Bachmann, Julien; Vogel, Nicolas (ACS Applied Materials and Interfaces, 2022)
Liquid-infused surfaces offer a versatile approach to create self-cleaning coatings. In such coatings, a thin film of a fluid lubricant homogeneously coats the substrate and thus prevents direct contact with a second, contaminating liquid. For stable repellency, the interfacial energies need to be controlled to ensure that the lubricant is not replaced by the contaminating liquid. Here, we introduce the concept of self-functionalizing lubricants. Functional molecular species that chemically match the lubricant but possess selective anchor groups are dissolved in the lubricant and self-adhere to the surface, forming the required surface chemistry in situ from within the applied lubricant layer. To add flexibility to the self-functionalizing concept, the substrate is first primed with a thin polydopamine base layer, which can be deposited to nearly any substrate material from aqueous solutions and retains reactivity toward electron-donating groups such as amines. The temporal progression of the in situ functionalization is investigated by ellipsometry and quartz crystal microbalance and correlated to macroscopic changes in contact angle and contact angle hysteresis. The flexibility of the approach is underlined by creating repellent coatings with various substrate/lubricant combinations. The prepared liquid-infused surfaces significantly reduce cement adhesion and provide easy-to-clean systems under real-world conditions on shoe soles.
CRIS-Team Scopus Importer:2022-04-22
Keywords: coatings; liquid-infused surfaces; polydopamine; self-cleaning; surface functionalization

Mechanical Stability of Liquid-Infused Surfaces Based on Mussel-Inspired Polydopamine Chemistry - Chiera, Salvatore; Ghetina, Melissa; Zimmermann, Thomas; Wintzheimer, Susanne; Stauch, Claudia; Loebmann, Peer; Mandel, Karl; Vogel, Nicolas (Macromolecular Materials and Engineering, 2023)
Liquid-infused surfaces exhibit remarkable repellency properties toward water, oils, and complex fluids and are widely applied to maintain clean, operational, and high-performing surfaces in various fields, from the biomedical sector to marine infrastructure. Polydopamine (PDA) forms an ideal base layer for the development of such coatings as it adheres to virtually any substrate and can be chemically modified via amino-containing molecules to adjust the surface properties. Here, strategies are explored to increase the mechanical stability of such coatings by i) incorporating imidazole during film formation to increase crosslinking, and ii) formation of a composite consisting of the organic PDA and an inorganic siliceous porous coating by infiltration of a preformed porous silica layer with PDA. Both strategies exhibit improved resistance to tangential shear assessed by a sandpaper abrasion test and to dynamic impact assessed by a sand trickle test. These improved mechanical properties are successfully transferred to liquid-infused surfaces created from such modified PDA base layers. The most durable coatings retain efficient liquid repellency after 25 abrasion cycles, indicating improved resilience in real-world application
Keywords: liquid-infused surfaces; mechanical resistance; coatings; polydopamine; wetting

Substrate-Independent Design of Liquid-Infused Slippery Surfaces via Mussel-Inspired Chemistry - Chiera, Salvatore; Bittner, Carina; Vogel, Nicolas (Advanced Materials Interfaces, 2021)
Self-cleaning and repellent coatings ensure enduring performance of surfaces in many areas of technology and everyday life. An ideal repellent coating is efficient in removing contaminations, yet easy to apply on a wide range of surface materials. To devise such a coating, two bioinspirations are combined that show opposing interfacial properties: the peristome of a pitcher plant and the versatile mussel-inspired chemistry of polydopamine (PDA). The possibility of PDA to bind to different surface materials is taken to provide a material-independent coating strategy. Its reactivity toward amines to cofunctionalize the coating with monoaminopropyl-polydimethylsiloxane is utilized to control the surface chemistry. This process, in effect, adheres silicone polymer chains to any desired surface material. Finally, inert silicone oil is added to the reaction mixture to provide in situ lubrication of the coating. Together, the process creates lubricant-infused surfaces in a one-step process independent of the underlying substrate. It is shown that the reaction mixture can be deposited by dip or spray coating, providing procedures to coat large surfaces and complex samples such as textiles and wood. The combination of the mussel-inspired chemistry with the pitcher plant-inspired control of wettability provides an experimentally simple coating process to impart efficient repellency and self-cleaning characteristics to virtually any surface material.
CRIS-Team Scopus Importer:2021-05-14
Keywords: liquid infused surfaces; liquid repellency; mussel-inspired chemistry; polydopamine; slippery surfaces; spray coating

Versatile strategy for homogeneous drying patterns of dispersed particles - Rey, Marcel; Walter, Johannes; Harrer, Johannes; Perez, Carmen Morcillo; Chiera, Salvatore; Nair, Sharanya Sukumar; Ickler, Maret; Fuchs, Alesa; Michaud, Mark; Uttinger, Maximilian; Schofield, Andrew B.; Thijssen, Job H. J.; et al. (Nature Communications, 2022)
After spilling coffee, a tell-tale stain is left by the drying droplet. This universal phenomenon, known as the coffee ring effect, is observed independent of the dispersed material. However, for many technological processes such as coating techniques and ink-jet printing a uniform particle deposition is required and the coffee ring effect is a major drawback. Here, we present a simple and versatile strategy to achieve homogeneous drying patterns using surface-modified particle dispersions. High-molecular weight surface-active polymers that physisorb onto the particle surfaces provide enhanced steric stabilization and prevent accumulation and pinning at the droplet edge. In addition, in the absence of free polymer in the dispersion, the surface modification strongly enhances the particle adsorption to the air/liquid interface, where they experience a thermal Marangoni backflow towards the apex of the drop, leading to uniform particle deposition after drying. The method is independent of particle shape and applicable to a variety of commercial pigment particles and different dispersion media, demonstrating the practicality of this work for everyday processes.
CRIS-Team WoS Importer:2022-06-10